(X+0.7)(x+3.4)=0

Simple and best practice solution for (X+0.7)(x+3.4)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (X+0.7)(x+3.4)=0 equation:


Simplifying
(X + 0.7)(x + 3.4) = 0

Reorder the terms:
(0.7 + X)(x + 3.4) = 0

Reorder the terms:
(0.7 + X)(3.4 + x) = 0

Multiply (0.7 + X) * (3.4 + x)
(0.7(3.4 + x) + X(3.4 + x)) = 0
((3.4 * 0.7 + x * 0.7) + X(3.4 + x)) = 0
((2.38 + 0.7x) + X(3.4 + x)) = 0
(2.38 + 0.7x + (3.4 * X + x * X)) = 0
(2.38 + 0.7x + (3.4X + xX)) = 0

Reorder the terms:
(2.38 + 3.4X + 0.7x + xX) = 0
(2.38 + 3.4X + 0.7x + xX) = 0

Solving
2.38 + 3.4X + 0.7x + xX = 0

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-2.38' to each side of the equation.
2.38 + 3.4X + 0.7x + -2.38 + xX = 0 + -2.38

Reorder the terms:
2.38 + -2.38 + 3.4X + 0.7x + xX = 0 + -2.38

Combine like terms: 2.38 + -2.38 = 0.00
0.00 + 3.4X + 0.7x + xX = 0 + -2.38
3.4X + 0.7x + xX = 0 + -2.38

Combine like terms: 0 + -2.38 = -2.38
3.4X + 0.7x + xX = -2.38

Add '-0.7x' to each side of the equation.
3.4X + 0.7x + -0.7x + xX = -2.38 + -0.7x

Combine like terms: 0.7x + -0.7x = 0.0
3.4X + 0.0 + xX = -2.38 + -0.7x
3.4X + xX = -2.38 + -0.7x

Reorder the terms:
2.38 + 3.4X + 0.7x + xX = -2.38 + -0.7x + 2.38 + 0.7x

Reorder the terms:
2.38 + 3.4X + 0.7x + xX = -2.38 + 2.38 + -0.7x + 0.7x

Combine like terms: -2.38 + 2.38 = 0.00
2.38 + 3.4X + 0.7x + xX = 0.00 + -0.7x + 0.7x
2.38 + 3.4X + 0.7x + xX = -0.7x + 0.7x

Combine like terms: -0.7x + 0.7x = 0.0
2.38 + 3.4X + 0.7x + xX = 0.0

The solution to this equation could not be determined.

See similar equations:

| (x+1)(4x-3)=2(x+1)(2x+3) | | 12600-s=925 | | 8x+8+6x+6=56 | | 4x-4=-8x+8x | | 4y-2=6(y+1) | | 0.35x+0.10(260-x)=43.5 | | 7x+3+7x+4=105 | | 3x+2+6x+9=92 | | x-6x+21=76 | | 3(x+2)+4=13 | | -5(n+7)=-115 | | 4(7-3y)+3y=13 | | 3c=13+9c | | X-2-(x+3)=2(x-4)-5 | | 8=-12-5q | | 14=2(1s+15) | | 1-3x=7x | | -5(7x-7)=140 | | 5[x+4]-4x=18-23 | | x^2-2x=54 | | 9=z-[-5] | | -33=9x+3 | | 7(7k+6)=91 | | -4y=-52 | | 15k=-120 | | -88=4(-7-3x) | | 3(X+6)-7=11 | | 66=2l+2*7 | | -(7z+10)=5z | | 3y+2xy=10 | | 7=-7(3+m) | | 64k^4= |

Equations solver categories